Recruitment Outcomes of a Pilot Randomized Controlled Trial of Tools for the Self-assessment and Management of Endometriosis-associated Deep Dyspareunia. (1st August 2022) - Wu, S; MacLeod, R; Parmar, K; Orr, N; Wahl, K; Albert, A; Brotto, L; Flannigan, R; Yong, P
ABSTRACT: Introduction: Deep dyspareunia negatively impacts people living with endometriosis and their sexual relationships. We are conducting a pilot study to assess the acceptability of 1) a silicone buffer (brand: OhNut) worn by the penetrating partner during intercourse to manage deep dyspareunia and 2) a vaginal insert for self-assessment of deep dyspareunia. The study is ongoing, and recruitment of participants is complete. Objective: To report recruitment outcomes for the ongoing study including response rate, consent rate, and percent screen failed by category. Methods: The recommended sample size was 24 couples; given potential dropout and uncertainty about the variance in acceptability, we aimed to recruit 40 couples. Potential patient participants were people with a surgical diagnosis of endometriosis at a tertiary care centre in Western Canada, who attended a clinic appointment between January 1, 2018, and December 31, 2020, and had previously consented to be contacted for research. We telephoned potential participants twice and then contacted them by email twice. Phone screenings were conducted for inclusion criteria in the following order: age 19-49, sexually active with a monogamous partner, superficial dyspareunia <4/10, deep dyspareunia ≧4/10, no prior use of a silicone buffer, no intense anxiety around sexual activity, GAD-7<15, and PHQ-9<15. Questions were asked sequentially until the first failed. Consent forms were then given for potential participants to review with their partners with a second phone call arranged to review any questions and informed consent. Recruitment stopped when we contacted each potentially eligible participant the maximum allowable number of times. 31 couples consented to participating in the study. Results: 2317 new patients attended a clinic appointment within the recruitment time frame, including 864 potentially eligible participants. The response rate was 45% (368 responses). Of respondents, 8% consented to participate, 65% were interested but did not meet inclusion/ exclusion criteria, and 27% declined participation. Of those who did not meet eligibility criteria, 8% had high superficial dyspareunia, 52% reported no or low deep dyspareunia, 21% had no monogamous sexual partner, 4% had a partner who declined participation, 5% did not have penetrative sex, 8% scored ≧ 15 on the GAD-7 or reported high anxiety around sexual activity, 0.4% had a PHQ-9 score ≧ 15, and 2% had previously used the silicone buffer. The recruitment rate was around 5 participants per month of active recruitment. Conclusions: Recruitment barriers in this pilot trial included no or low deep dyspareunia (likely related to previous treatment at the tertiary care centre, prior to recruitment); no monogamous partner; concurrent superficial dyspareunia; and high anxiety scores. Thus a future definitive trial should consider including subjects earlier in the treatment pathway, those who are unpartnered, and individuals who are experiencing concomitant superficial dyspareunia or anxiety. Disclosure: Yes, this is sponsored by industry/sponsor: OhNut Wearable - provided a discount on the silicon buffer used in the trial; ISSWSH Grant Clarification: No industry support in study design or execution